Volume 3: Turbo Expo 2005, Parts a and B 2005
DOI: 10.1115/gt2005-68036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Compound Angle on Adiabatic Film Cooling Effectiveness and Heat Transfer Coefficient for a Row of Shaped Film Cooling Holes

Abstract: The measurement of adiabatic film cooling effectiveness data and heat transfer coefficient data for a row of fanshaped film cooling holes at different compound angles is presented in this paper. The measurements are performed at engine-like temperature ratios in a hot gas test facility on a flat test plate. For the film cooling geometry, a row of five laidback-fanshaped holes was used. The temperature distribution on the flat plate is measured using infrared-thermography (IR). Steady state measurements are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Regarding the external film cooling. Brauckmann and Wolfersdorf [13] and Aga et al [14] showed improvements on the thermal protection of the blade, using cooling holes with expanded exits (compound angle) aiming to reduce the momentum of the jel as well as to align the film-cooling traces on the blade. In addition, Hu and Ji [15] investigated, numerically, the eftect of blowing angle, illustrating that increased film-cooling effectiveness is achieved at higher blowing angles.…”
Section: Effects Of Swirl Velocities From Fan Assemblies Mounted On Lmentioning
confidence: 99%
“…Regarding the external film cooling. Brauckmann and Wolfersdorf [13] and Aga et al [14] showed improvements on the thermal protection of the blade, using cooling holes with expanded exits (compound angle) aiming to reduce the momentum of the jel as well as to align the film-cooling traces on the blade. In addition, Hu and Ji [15] investigated, numerically, the eftect of blowing angle, illustrating that increased film-cooling effectiveness is achieved at higher blowing angles.…”
Section: Effects Of Swirl Velocities From Fan Assemblies Mounted On Lmentioning
confidence: 99%
“…To overcome the weakness of the cylindrical holes, the effects of shaped holes have been studied [3][4][5][6]. The shaped holes are designed to enhance the lateral spreading of the coolant because neighboring coolant jets immediately start merging downstream of the injection.…”
Section: Introductionmentioning
confidence: 99%
“…Baheri et al [5] numerically investigated the effect of the trench on the film-cooling effectiveness for the cylindrical and the shaped holes with and without the trench, and reported that the trench-shaped hole showed the best cooling performance. The experimental data of a shaped hole presented by Brauckmann and Wolfersdorf [6] represents the effects of the compound angle and blowing ratio on the heat transfer coefficient and the film-cooling effectiveness. They reported that the variation of the compound angles hardly affected the film-cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Brauckmann 과 Wolfersdorf (4) 는 측면 방향 분사각이 0, 30, 45°인 홴형상 홀에 대해 분사율이 0.5, 1, 1.5, 2 일 때의 막냉각 효율과 열전달계수에 대해 평가하였으 며, 측면 방향 분사각이 측면 방향 평균 막냉각 효 율에는 작은 영향만을 주었으나 막냉각 표면에서의 열전달은 증가되었다고 보고하였다. Nasir 등 (5) 는 측 면 방향 분사각이 0, 60° 인 원통형 막냉각 홀에 대 해 분사율을 0.5, 1.0, 1.5 로 변화시키며 연구를 수행 하였으며, 측면 방향 분사각이 막냉각 효율에 중요 한 변화를 주며 열전달계수를 높인다고 평가하였다.…”
unclassified